2022
DOI: 10.2340/jrm.v54.2162
|View full text |Cite
|
Sign up to set email alerts
|

Caregiving, Participation, and Quality of Life of Closest Next of Kin of Persons Living with Spinal Cord Injury in Norway

Abstract: Objectives: To investigate how next of kin of persons with spinal cord injury (SCI) experience various life areas in terms of caregiving, participation, and quality of life (QoL), and the impact of personal characteristics of next of kin and SCI characteristics. Design: Survey among next of kin linked to data on persons with SCI in the Norwegian SCI Registry. Participants: Seventy-three next of kin identified by a person with SCI. Methods: The outcome measures were caregiving (4 measures), pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…On the Emotional Involvement subscale, we found that female caregivers reported higher levels of burden. This has also been reported in an SCI group previously ( 2 ), but the opposite pattern has also been reported among stroke caregivers, where males reported higher burden ( 41 ). But as already mentioned, most studies have found no association between gender and burden ( 23 , 32 , 35 , 38 , 42 , 43 ).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…On the Emotional Involvement subscale, we found that female caregivers reported higher levels of burden. This has also been reported in an SCI group previously ( 2 ), but the opposite pattern has also been reported among stroke caregivers, where males reported higher burden ( 41 ). But as already mentioned, most studies have found no association between gender and burden ( 23 , 32 , 35 , 38 , 42 , 43 ).…”
Section: Discussionsupporting
confidence: 77%
“…A fter a neurological condition such as stroke, spinal cord injury (SCI), or traumatic brain injury (TBI), life is dramatically disrupted for the person concerned and their family members (1)(2)(3). Most of these individuals experience short and long-term physical, emotional, and cognitive sequelae that cause them to require some level of assistance to do everyday activities.…”
mentioning
confidence: 99%
“…Relatives (kins/cousins) were also found to be primary caregivers, and the spouses of male SCI people, as well as the mothers of female SCI individuals, were primarily active in caretaking among family members, if the individual was married. A study on various aspects of caregivers' lives showed age and educational status have a significant relationship among them [ 26 ]. In contrast, caregivers' educational attainment varied considerably in terms of proportions at the higher education level [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that spouses of individuals with SCI who express a positive attitude towards caring have improved emotional wellbeing. Additional studies on the positive features of caring are thus necessary in the future [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation